2006
DOI: 10.1001/archpsyc.63.5.509
|View full text |Cite
|
Sign up to set email alerts
|

Major Depressive Episodes and Random Mood

Abstract: Time-to-event data from psychiatric epidemiologic studies can be conceptualized through modeling as intrasubject processes. The proposed random-mood model reproduces the time-to-event data and explains the incubation phase as an artifact due to the inclusion criterion of 14 days in most current psychiatric diagnostic systems. Depression is found to result more often from pileup of negative stimuli than from single life events. Time sequences, generated using the random-mood model, produce power plots, phase-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…The probability to relapse decreases over time. Recovery and relapse curves were estimated based on data from the Dutch NEMESIS study, and an Australian modelling study [19], [20]. These probability curves are presented in figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…The probability to relapse decreases over time. Recovery and relapse curves were estimated based on data from the Dutch NEMESIS study, and an Australian modelling study [19], [20]. These probability curves are presented in figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…This model provides a mathematical framework for enhanced signal detection and classification and is consistent with clinical observations in untreated healthy normal subjects. Even though stochastic calculus is ubiquitous in finance and economics, it is largely untapped in the biological sciences, especially in clinical medicine [1,3,10,14,17,23,24,29,30]. The use of a qdimensional ðq -pÞ Brownian motion process to describe the driving force of the biological system could be very useful.…”
Section: Discussionmentioning
confidence: 99%
“…By far, most of the depressive episodes are reversible: meaning that in the general population with or without professional therapeutic interventions, about 80% recovers (Spijker et al 2002) We measured and modeled the incidence of recovery of a depressive cohort extracted from the general population with or without comorbid psychiatric or somatic pathology (van der Werf et al 2006; Kaptein et al 2007). It appeared that the rate of recovery follows an exponential time course, indicating that the probability to recover from depression is independent of the length of the depressive episode.…”
Section: Causality and The Brainmentioning
confidence: 99%
“…The model showed that the 2-week criterion of the DSM is rather arbitrary and not a characteristic (i.e. an ‘incubation period’) for major depression (van der Werf et al 2006; Kaptein et al 2007). Results on hospitalised depressed patients (e.g.…”
Section: Causality and The Brainmentioning
confidence: 99%